Results of tetanus vaccination in sarcoidosis - Seyhan, E.C.; Günlüoğlu, G.; Altin, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background and Objective: Cellular immunity abnormalities are associated with sarcoidosis. Normal cellular immunity is required for adequate humoral immunity; therefore, a decreased humoral immune response is possible in patients with sarcoidosis.We evaluated humoral immunity by vaccinating patients with sarcoidosis against tetanus. Patients and method: We screened 60 patients with sarcoidosis (42 females, average age 39 ± 11 years) and 40 healthy subjects as a control (23 females, average age 38 ± 9 years). Of the 51 sarcoidosis patients and 33 controls that did not have sufficient tetanus antibody titers, 48 patients and 31 controls agreed to be vaccinated and were included in the vaccination program. Blood serum samples were collected from the subjects before and after vaccination and evaluated for tetanus toxoid IgG antibodies with an enzymelinked immunosorbent assay (ELISA). Results: As a result of the vaccination, 24 of the sarcoidosis patients (50%) and 7 of the controls (23%) had insufficient antibody responses (p = 0.019). No relationship was found in sarcoidosis patients between the rate of having sufficient antibody levels and disease duration, activation state, and radiographic staging of the disease. Conversely, mean lymphocyte numbers were significantly lower in patients with insufficient tetanus antibody levels (p = 0.013). Conclusion: Tetanus vaccinations in sarcoidosis patients are less effective than in healthy controls, suggesting that patients with sarcoidosis have a hyporesponsive humoral immune system.